Study of Image Resolution in Virtual Reality Panorama Technology 360 In Comfort of Interior Visualization - Pramalystianto, Andhika (International Journal of Architecture and Urbanism, 2023)
Utilizing virtual reality technology is used as a method of interacting virtually. With the many uses of virtual reality today, it certainly affects the lives of users of these technologies. In the field of interior design itself, virtual reality technology is also often used, the application of VR technology for design interior are often used as a means of design presentation. This study is aimed at testing the visual comfort of virtual reality panorama 360 which is used as a medium for virtual interaction of interior design to interior design users. The analysis process in taking data by questionnaire and followed by several stages of observation and the last stage is the experimental stage to take research data related to case studies. The results obtained from this study are knowing visual comfort when interacting directly using virtual reality technology. It is hoped that with the testing of the visual resolution used in interior virtual reality, it can later be used as a reference in the selection of visual media in the future.